Antimicrobial Activity of Extracts from the Humiria balsamifera (Aubl) - Edelson de J. S. Dias; Antônio J. Cantanhede Filho; Fernando J. C. Carneiro; Cláudia Q. da Rocha; Luís Cláudio N. da Silva; Joice C. B. Santos; Thayná F. Barros; Deivid M. Santos (Plants, 2021)
Humiria balsamifera (Aubl), commonly known as “mirim”, is a plant of the Humiriaceae family, which consists of 39 species divided between eight genera: Duckesia, Endopleura, Humiria, Humiriastrum, Hylocara, Sacoglottis, Schistostemon, and Vantenea. This study aimed to characterize H. balsamifera extracts by LC-MS/MS and evaluate their antimicrobial potential through in vitro and in vivo assays. The leaves and stem bark of H. balsamifera were collected and dried at room temperature and then ground in a knife mill. The extracts were prepared with organic solvents in order to increase the polarity index (hexane, ethyl acetate, and methanol). The antimicrobial effects of these extracts were evaluated against the following bacterial strains: Escherichia coli ATCC 25922, Listeria monocytogenes ATCC 15313, Salmonella enterica Typhimurium ATCC 14028, and Staphylococcus aureus ATCC 6538. The best activity was observed in the ethyl acetate (EALE = 780 µg/mL), methanol (MLE = 780 µg/mL), and hexane (HLE = 1560 µg/mL) leaf extracts against S. aureus. Considering the results for both antimicrobial and antibiofilm activities, the EALE extract was chosen to proceed to the infection assays, which used Tenebrio molitor larvae. The EALE treatment was able to extend the average lifespan of the larvae (6.5 days) in comparison to S. aureus-infected larvae (1 day). Next, the samples were characterized by High-Performance Liquid Chromatography coupled to a mass spectrometer, allowing the identification of 11 substances, including seven flavonoids, substances whose antimicrobial activity is already well-reported in the literature. The number of bioactive compounds found in the chemical composition of H. balsamifera emphasizes its significance in both traditional medicine and scientific research that studies new treatments based on substances from the Brazilian flora.